Nicolau de Cusa: visão de Deus e teoria do conhecimento - Lyra, Sonia Regina (2010)
God is the target and the quest of Nicholas of Cusa s theory of knowledge. Disjunction and conjunction constitute the wall of coincidence of opposites beyond which God exists, unlinked of everything that can be said or thought. The daring characteristic of the Cusan proposal is in putting forward the enigma, highly speculative, of seeing the invisible through the created visible things, which is sought in an invisible way especially in his works De Docta Ignorantia (Of Learned Ignorance) and De visione Dei (On the Vision of God). The non-other one of the most accurate names according to Nicholas of Cusa to denominate the unnamable had already been predicted by Dionysius the Areopagite at the end of his De Mystica Theologia (Mystical Theology). Every concept, every definition is, therefore, conjectural about the first principle. Defining is setting limits and, above all, knowing, even though the definition itself cannot be determined by anything due to its anteriority. Once it is the definition that allows the excellence of knowledge, setting limits and determinations, the search for learned ignorance, which accompanies the path of theory, goes on circumscribing knowledge and leaving aside everything that it is not, following a negative theology. Considered as self-defining of itself in its ontological principle, the definition differentiates itself as a statement of reason and as a gnosiological principle. It is then that the discourse allows imposing a conceptual limit in relation to the thing and to what it is not. Being the first principle, intellectual principle, it is not possible to have as an object of thought anything other than itself and, with this, it is the sole principle of being and of knowing - principium essendi et cognoscendi. The mystical dimension of this theory of knowledge can be seen in De visione Dei (On the Vision of God), where Cusa prepares and indicates the path to be traveled from the sensitive point to the transumptive jump beyond the wall of coincidence of opposites. Understood as imago Dei, man has in parallel with the divine mind the humana mens, even though this notion implies in showing the inadequacy of the image in relation to its specimen